1983
DOI: 10.2307/2387833
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of River-Created Habitats to Bird Species Richness in Amazonia

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The Association for Tropical Biology and Conservation is collaborating with JSTOR to digitize, preserve and extend access to Biotropica. ABSTRACT A substantial portion (15%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
190
1
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(222 citation statements)
references
References 10 publications
4
190
1
10
Order By: Relevance
“…So, the flooding periods in the Brazilian Atlantic forest would not increase significantly the number of microhabitats, as occurs in the larger Amazonian rivers, where flooding periods take several months and cover large areas (KARR & ROTH 1971, REMSEN & PARKER 1983. However, the pulses of nutrients and energy may have impacts on the food supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the flooding periods in the Brazilian Atlantic forest would not increase significantly the number of microhabitats, as occurs in the larger Amazonian rivers, where flooding periods take several months and cover large areas (KARR & ROTH 1971, REMSEN & PARKER 1983. However, the pulses of nutrients and energy may have impacts on the food supply.…”
Section: Discussionmentioning
confidence: 99%
“…ing to the unrivaled avian richness observed in Amazonian lowlands (REMSEN & PARKER 1983, ROBINSON & TERBORGH 1997. However, the importance of surrounding forest of streams and rivers for bird communities and abundance in Brazilian Atlantic Forest has received less attention.…”
Section: Resumo Amentioning
confidence: 99%
“…5). For example, dispersion fields in Amazonia are significantly influenced by the distributions of Ϸ70 nonaquatic species that are restricted to riverine habitats in the Amazon-Orinoco-Guiana lowlands (45). In general, the asymmetry of dispersion fields increases from the center to the perimeter of spatially extensive biomes as a result of nonrandom sampling of the regional species pool.…”
Section: Assemblage Dispersion Fields Are Asymmetrical and Exhibit Comentioning
confidence: 99%
“…It has been suggested that local variations in the forest structure may be important ecological factors affecting their habitat use (ORIANS 1969, WILLIS 1977, REMSEN & PARKER 1983, TERBORGH 1985, KARR et al 1990, TERBORGH et al 1990, CINTRA 1997, BORGES et al 1999, CINTRA et al 2006, BANKS & CINTRA 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on habitat use by birds in tropical rainforests have also focused on factors affecting richness and abundance of species and most of the studies on effects of vegetation on birds have concentrated on habitat partitioning by species (REMSEN & PARKER 1983, TERBORGH 1985, and on the effects of vegetation structure on bird guilds or communities (PEARSON 1975, HOWE & SMALLWOOD 1982, TERBORGH et al 1990, LOISELLE & BLAKE 1991. However, few studies have investigated how micro-habitat structure and resource availability affect individual species (but see TERBORGH 1985, CINTRA 1997.…”
Section: Resumo Efmentioning
confidence: 99%